Competency based primary education curriculum of Bangladesh: SDG - K M Obaydullah, A; Jahan, Nusrat (SPC Journal of Education, 2020)
Education now is first time truly aiming to improve access to quality education on sustainable development to develop knowledge and skills required for sustainable development. Many countries in Asia are transforming institutions as â€˜Thinking Schoolsâ€™. The government of Bangladesh, just like other countries, because of the impact of globalization, it has continued to reform education sector to respond to more emerging issues towards sustainable development. It is on this premise that the introduction of new education system. However, there is too little which has been done in establishing the link between competencies based curriculum and sustainable development and their teething challenges. This article is purposed to link competency based learning curriculum to sustainable development, while bringing to the fore the challenges the Competency Based Curriculum (CBC) is contenting with from conception to its implementation phase and their possible panaceas. Specifically and chronologically, this reflective article attempts clarification of key operational terminologies used, link between competencies and sustainable development, Role of CBC in SDG, theoretical underpinnings of CBC, challenges of CBC, conclusions and recommendations. This reflective and theoretical article significantly contributes to the ongoing debates and reflections on the contribution of competency based curriculum on sustainable development, while addressing the teething challenges undermining the CBC implementation with a view of making it acceptable to all and providing apt strategies towards its successful implementation. Bangladesh is on its way to achieving a Middle Income Country (MIC) status in 2021 and will become a developed country by 2041.Â Â